Temporary basolateral amygdala lesions disrupt acquisition of socially transmitted food preferences in rats - Wang, Yunyan (Cold Spring Harbor Laboratory Press, 2006)
Lesions of the basolateral amygdala (BLA) have long been associated with abnormalities of taste-related behaviors and with failure in a variety of taste- and odor-related learning paradigms, including taste-potentiated odor aversion, conditioned taste preference, and conditioned taste aversion. Still, the general role of the amygdala in chemosensory learning remains somewhat controversial. In particular, it has been suggested that the amygdala may not be involved in a form of chemosensory learning that has recently received a substantial amount of study—socially transmitted food preference (STFP). Here, we provide evidence for this involvement by pharmacologically inactivating the basolateral amygdala bilaterally during STFP training. The same inactivation sites that impaired taste aversion learning eliminated the normally conditioned preference for a food smelled on a conspecific’s breath. Impairments of learned preference persisted even in testing sessions in which BLA was not inactivated, and learning was normal when the BLA was inactivated only during testing sessions; thus, the impairment was a true acquisition deficit. In conjunction with previous results from other paradigms, therefore, our data suggest that the amygdala is vital for learning procedures involving pairings of potent and arbitrary chemosensory stimuli.